A Philosophical Study of the Weton Tradition Calculation in Javanese Marriage - Ratnasari, Deshinta (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This scientific work investigates the ingrained Javanese weton calculation custom, which determines the wedding day. The implication of this research is the need to understand the application of the weton calculation tradition in Javanese marriages. because with the application of the weton calculation tradition, it will make it easier for prospective brides who will marry in their new lives and be more sensitive to the problems that exist around their environment because in marriage, especially regarding the weton tradition, people are quite diverse in expressing their perceptions. Weton calculation is also considered as an effort and a form to reduce doubts about the durability of the couple's relationship in the future because life is always spinning so the principle of caution must be applied. Three ancient calendars that are often used by Javanese people to calculate weton calculations include the Saka calendar, the Sultan Agung calendar, and the Pranatatani calendar. Weton is categorized as a munkar al-'urf al fasid custom or practice if it is considered an antidote to bad luck and a way to ward off bad luck. Islam uses the term